Trial watch: DNA-based vaccines for oncological indications. (2nd December 2017) - Pierini, Stefano; Perales-Linares, Renzo; Uribe-Herranz, Mireia; Pol, Jonathan G.; Zitvogel, Laurence; Kroemer, Guido; Facciabene, Andrea; Galluzzi, Lorenzo
ABSTRACT: DNA-based vaccination is a promising approach to cancer immunotherapy. DNA-based vaccines specific for tumor-associated antigens (TAAs) are indeed relatively simple to produce, cost-efficient and well tolerated. However, the clinical efficacy of DNA-based vaccines for cancer therapy is considerably limited by central and peripheral tolerance. During the past decade, considerable efforts have been devoted to the development and characterization of novel DNA-based vaccines that would circumvent this obstacle. In this setting, particular attention has been dedicated to the route of administration, expression of modified TAAs, co-expression of immunostimulatory molecules, and co-delivery of immune checkpoint blockers. Here, we review preclinical and clinical progress on DNA-based vaccines for cancer therapy.